2021
DOI: 10.9745/ghsp-d-20-00429
|View full text |Cite
|
Sign up to set email alerts
|

The Community Health Systems Reform Cycle: Strengthening the Integration of Community Health Worker Programs Through an Institutional Reform Perspective

Abstract: Despite strong interest and policy commitments from many countries, models for community-based primary health service delivery have been slow to achieve full scale or deliver quality that matches their potential. n Reform requires a carefully choreographed effort to enroll key stakeholders to support change by spotlighting a locally relevant gap in the existing health system's performance. n Designing and launching community health programs depends heavily on local context and must draw from models that are av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…16 Chen et al describe how the institutional health reform cycle can guide policy makers in identifying gaps and opportunities while coordinating input from multiple stakeholders to extend CHW program coverage. 17 These studies provide additional evidence that the likelihood of achieving the SDGs increases as coverage of underserved populations accessing lifesaving interventions and commodities improves.…”
Section: Coverage Of Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…16 Chen et al describe how the institutional health reform cycle can guide policy makers in identifying gaps and opportunities while coordinating input from multiple stakeholders to extend CHW program coverage. 17 These studies provide additional evidence that the likelihood of achieving the SDGs increases as coverage of underserved populations accessing lifesaving interventions and commodities improves.…”
Section: Coverage Of Populationsmentioning
confidence: 99%
“…20 Consistent with that accelerating shift, financing is described as a critical bottleneck to achieving maturity and scale in several articles. 15,17,18,21 Saint-Firmin et al analyze the distribution of reported expenditure, efficiency, and geospatial mapping in Mali to inform decision makers in transitioning to a domestically funded CHW program. 22 They demonstrate where efficiencies could be found and targeted geographically to reach underserved communities.…”
Section: Community Health Financingmentioning
confidence: 99%
See 2 more Smart Citations
“…(12) There are different reasons for this, from a lack of political will, no finances to scale up, to ill-fitting health policies and unsuccessful pilot programs. (13) There is a surprising lack of in-depth studies that provide guidance to programme designers or could be used to create evidence-based policies. (14) Little research has been conducted into community motivation as a factor that can significantly influence the sustainability of volunteers.…”
Section: Introductionmentioning
confidence: 99%